Effect of Reaction Temperature and the CPO/Metanol Ratio on the Product Characteristics in the Biodiesel Production Using Diethyl Eter as Co-Solvent - Puguh Setyopratomo; Edy Purwanto; Rudy Hartanto; J Kristianto (Jurnal ILMU DASAR, 2008)
In this research Crude Palm Oil (CPO) and methanol were reacted by applying 5 % basic catalyst (KOH) and adding diethyl ether as co-solvent to produce methyl ester (biodiesel). Co-solvent was added in order to form one-phase reaction mixture, and then higher reaction rate was expected compare with two-phase system. Reaction was carried out batch wise in 1 litre glass reactor stirred continuously at 300 rpm. The objective of this research is to obtain the characteristic of biodiesel product. The advantage using this methode was showed by several characteristics of the biodiesel product. The density and viscosity had achieved the commercial biodiesel standard, this biodiesel product has higher flash point of the product compared with solar, which means lower risk factor during storage. The very low sulfur content and the pour point of product that was layed below the maximum allowable limit, are environmentally favorable.